The future of food safety in Africa: Research perspective - Grace, Delia; Alonso, Silvia; Amenu, K.; Cook, Elizabeth A.J.; Dione, Michel M.; Knight-Jones, Theodore J.D.; Lindahl, Johanna F.; Mutua, Florence K.; Hung Nguyen-Viet; Roesel, Kristina; Thomas, Lian F. (International Livestock Research Institute, 2021)
The last decades have seen immense progress in food safety in Africa: the coming decades offer more. We summarise recent and ongoing food safety research, carried out by the International Livestock Research Institute and its partners. This is organised in four areas. First is generating evidence on food-borne disease burdens to support decision making. We are helping update the landmark WHO report and giving country specific estimates. We helped estimate the economic burden of foodborne disease at $17 billion USD per year for Africa. We are also conducting systematic literature reviews to generate best evidence on the priority hazards in Africa and the most effective interventions. An important impact pathway is in providing technical support to the African Union in its ground-breaking first regional food safety index. We have also helped review the AU food safety strategy and led food safety the UNFSS. Second is strengthening food safety education in Africa through benchmarking a curriculum on food safety, providing blended training on risk assessment for professionals, hands-on training for value chain actors, and supporting graduate fellows. Innovation is a key function of research, and we are currently integrating One Health into Community-Led Total Sanitation, developing and testing “behavioural nudges” in Uganda and Kenya and conducting experiments in using binders to reduce aflatoxins in dairy feed and hence in cow milk for human consumption. These contribute to the most important impact of research: safer food at scale. Interventions to improve food safety at scale in east and west Africa. Here we mention research on upgrading value chains and our flagship “three-legged stool approach” to improving food safety in informal markets by empowering consumers to demand safe food, vendors to provide it, and policymakers to support it.